Digital fabrication in architecture - Dunn, Nick, 1974- (London : Laurence King Publishing, 2012)
With the increasing sophistication of CAD and other design software, there is now a wide array of means for both designing and fabricating architecture and its components. This book focuses on the possibilities for architecture that can be achieved with all the different technologies and techniques available.
Includes bibliographical references and index.
includes index.
Keywords: AutoCAD; Architectural design -- Data processing; Computer-aided design